Academic Dishonesty in University of Education, Winneba: Prevalence, Penalties and Prevention - Abban, Kenneth (Ghana Journal of Higher Education Management, 2024)
The aim of this survey was to determine the prevalence, penalties and remedies for academic dishonesty in University of Education, Winneba. Results indicate a higher tolerance for academic misconduct by students in comparison to staff, particularly with respect to falsification of research results and plagiarism, as well as considerable underestimation by staff of the prevalence of virtually all forms of student academic misconduct. Mechanism for managing and curtailing the level of academic misconduct, are suggested.